Toxicity, baseline of susceptibility, detoxifying mechanism and sublethal effects of chlorogenic acid, a potential botanical insecticide, on Bemisia tabaci - Wang, Ran; Zhang, Qinghe; Qu, Cheng; Wang, Qian; Wang, Jinda; Luo, Chen (Frontiers in Plant Science, 2023)
Bemisia tabaci is a threat to agriculture worldwide because of its potential to cause devastating damage to crops. Chlorogenic acid is a bioactive pesticidal phytochemical agent against various insect pests. We here determined the susceptibility of a laboratory strain of B. tabaci to chlorogenic acid and other popular insecticides, and the susceptibility of several field-collected populations to chlorogenic acid. Also, cross-resistance to four common insecticides was measured. Chlorogenic acid had the highest toxicity of all tested insecticides, and all the field-collected populations were susceptible to chlorogenic acid, and little cross-resistance was detected between chlorogenic acid and the other tested insecticides. Furthermore, analysis of enzyme activities and expression of P450 genes in B. tabaci after treatment with LC50 of chlorogenic acid suggested that enhanced P450 activity could be involved in chlorogenic acid detoxification. We subsequently evaluated sublethal effects of chlorogenic acid, and found that treatment with LC25 of chlorogenic acid prolonged duration of two developmental stages, reduced fecundity, and decreased survival rates of treated B. tabaci compared to untreated insects. Overall, these findings demonstrate strong toxicity and significant sublethal effects of chlorogenic acid on B. tabaci, and suggest that overexpression of P450 genes may be associated with chlorogenic acid detoxification.